Predicting the solubility of pharmaceutical compound in ionic liquids using COSMo-RS model - Lotfi, M. (Asian Research Publishing Network, 2016)
One conventional way to address the poor solubility of drugs in order to increase their performance is to use excipients polar organic solvents. However, the use of such organic solvents has many drawbacks. They are often volatile, flammable and toxic. Pharmaceutical ingredients must be free from all such traces. So in this work, we have showed that we can use ionic liquids (ILs) as a replacement for conventional solvent in pharmaceutical industries. The solubility of Acyclovir in ILs was studied within two cations groups of ILs (Ammonium, Pyridinium) and sixteen anions using COSMOtherm-X software at room temperature and atmosphere pressure. COSMO-RS (Conductor like Screening Model for Realistic Solvents) program allows the prediction of many properties of pure fluids, fluid mixtures, and solutions. The results showed that the solubility of Acyclovir in ammonium-based ILs is relatively higher than other studied ILs. Considering ammonium salts examined in this work, tetramethylammonium-acetate N1111 OAc, trimethylethylammonium-acetate N1112 OAc and dimethylethylpropylammonium-acetate N1123 OAc are excellent solvents. Due to the increasing of side alkyl chain (methyl) and proper solubility toward the drug compound, makes them suitable for further studies. Â© 2006-2016 Asian Research Publishing Network (ARPN). All rights reserved.